Termodinâmica de buracos negros de Schwarzschild - Santi, Natali Soler Matubaro de (2018)
This dissertation consists of a review about some aspects of Schwarzschild black hole thermodynamics and includes a discussion related to the temporal evolution of the masses of these black holes in a thermodynamic context. We started studying some aspects of general relativity, verifying some properties first in Minkowski space-time, from perspective of an accelerated observer, and then in Schwarzschild space-time. After that we moved to quantum field theory in curved spaces, starting with the Unruh effect as a motivation for the Hawking radiation, which is the main goal of this work, deducing the temperature for a Schwarzschild black hole. Later we presented the laws of the black hole thermodynamics and an analogy with classical thermodynamics laws. Lastly, we discussed the temporal evolution of the masses of Schwarzschild black holes for different initial values and environment conditions: empty space, cosmic microwave background with constant temperature and with temperature varying with time according with the eras of the universe.